2020
DOI: 10.1186/s12989-020-00371-1
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube filler enhances incinerated thermoplastics-induced cytotoxicity and metabolic disruption in vitro

Abstract: Background: Engineered nanomaterials are increasingly being incorporated into synthetic materials as fillers and additives. The potential pathological effects of end-of-lifecycle recycling and disposal of virgin and nano-enabled composites have not been adequately addressed, particularly following incineration. The current investigation aims to characterize the cytotoxicity of incinerated virgin thermoplastics vs. incinerated nano-enabled thermoplastic composites on two in vitro pulmonary models. Ultrafine par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…Compounding this issue, significant gaps in knowledge remain about mechanisms of resazurin and tetrazolium metabolism, even though several groups have contributed significantly to the understanding of these endpoints 57 – 60 . Initially, our laboratory had observed robust hyperstimulatory WST1 metabolism during cytotoxicity screening of incinerated thermoplastic samples 61 similar to those observed with organic extracts of diesel exhaust particles 62 . Zhu et al 63 observed that micromolar B[a]P concentrations induced hyperstimulatory MTT metabolism similar to the current investigation, thus prompting this examination.…”
Section: Discussionmentioning
confidence: 56%
“…Compounding this issue, significant gaps in knowledge remain about mechanisms of resazurin and tetrazolium metabolism, even though several groups have contributed significantly to the understanding of these endpoints 57 – 60 . Initially, our laboratory had observed robust hyperstimulatory WST1 metabolism during cytotoxicity screening of incinerated thermoplastic samples 61 similar to those observed with organic extracts of diesel exhaust particles 62 . Zhu et al 63 observed that micromolar B[a]P concentrations induced hyperstimulatory MTT metabolism similar to the current investigation, thus prompting this examination.…”
Section: Discussionmentioning
confidence: 56%
“…Particle suspensions were immediately serially diluted in Roswell Park Memorial Institute + 10% FBS (RPMI) THP-1 cell culture medium. Media density, viscosity, and refractive index (Additional file 3 : Table S1) were determined using a volumetric flask with balance, viscometer, and a refractometer following previously described methods (n = 3 independent experiments) [ 40 ] and were used as input parameters to calculate hydrodynamic diameter via dynamic light scattering analysis (DLS). Effective density (ρ EV ) of each particle (0.1 mg/ml) in medium was measured using particle density, packed pellet volume, medium density, and theoretical stacking factor (SF = 0.634) as previously described (n = 3) [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Media density, viscosity, and refractive index (Additional file 3 : Table S1) were determined using a volumetric flask with balance, viscometer, and a refractometer following previously described methods (n = 3 independent experiments) [ 40 ] and were used as input parameters to calculate hydrodynamic diameter via dynamic light scattering analysis (DLS). Effective density (ρ EV ) of each particle (0.1 mg/ml) in medium was measured using particle density, packed pellet volume, medium density, and theoretical stacking factor (SF = 0.634) as previously described (n = 3) [ 40 , 41 ]. Soluble endotoxin in sonicated stock suspensions (n = 3) were determined with the Pierce LAL chromogenic method as previously described (ThermoFisher Scientific, Waltham, MA) [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Carbon nanotubes have been demonstrated to induce oxidative stress and inflammation, evidenced by the increased ROS in exposed cells. 78 Different types of CNTs exhibit varying levels of cytotoxicity, depended on factors such as concentrations and functionalization. 79,80 For example, carboxylic-functionalized CNTs have been reported to demonstrate higher cell viability compared to pristine CNTs in neuronal cells, LN18 at concentration up to 40 μg mL −1 and after longer incubation period (48 h).…”
Section: Other Carbon-based Photothermal Agent Containing Smpumentioning
confidence: 99%